O videoclipe no horizonte de expectativas do gênero musical - Soares, Thiago (2005)
The present article aims to explore music videos from the conventions of musical genres. Our intention is to perceive how the study of generic labels can contribute in the identification of a horizon of expectations in the public who watches music videos and, with this, generate certain parameters in the producing instances of this audiovisual. We consider to perceive, through concepts brought from Simon Frith, Jeder Janotti Jr and Andrew Goodwin, how music video is a device from the marketing configurations in pop music, being subject of economic, semiotic and technician principles of music industry.